Pembuatan Sistem Layanan Penjualan Berbasis Desktop Dilengkapi Monitoring Berbasis Android - Pringgo Juni Saputro; Nanik Nuryantini (Universitas Darussalam Gontor, 2016)
Sales service system is an information system that serves all activities relating to the sale, whether it's a sales transaction data processing, data processing, data processing purchase transactions of goods, processing of customer data, and the processing of data member supplier. Sales system that is currently developing in community is not yet integrated with mobile applications, resulting in the creation of reports, the incoming transaction cannot be monitored in real-time so that owners of companies that are outside the area or you're not at home, not able to keep an eye on sales transactions that occurred o their company. The purpose of this research is to provide ease of data processing at the time the goods, customer and supplier, ease in data processing sales and purchase transactions, minimize errors in recording data of purchase and sales data per period. The method of research done by two methods i.e., methods of data collection and the development of information systems. Method of data collection is done in finding the needed information with the activities of field studies and research librarian ship. Information systems development methods used in the assessment of the problem in data collection, this method of the form of Action Research, analysis, design, designing, implementation. Sales service system was built in order to provide ease in data processing sales and purchase either from sales to customers and purchases against the supplier as well as processing sale and purchase report making it more precise and accurate.